Effectiveness of PDI CSI (customer service inventory) as a screening tool for customer service positions in the local retailing industry. - Choy, Ginggi Mun Yee. (2008)
A pre-employment test, the Customer Service Inventory (CSI), was developed by Personnel Decisions, Inc. (PDI) to identify applicants with the desirable personality traits and skills required to fill these customer service positions. Our study’s main objective is, thus, to validate the use of this CSI tool in Singapore, specifically in the retailing industry.